Grain Sorghum Cost-Return Budget in South Central Kansas - Warmann, Gerald W. (My University, 1997)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in south central Kansas.
MF575_1997_10
Keywords: MF575; Economics; Crops; MF